Community based programme in meeting the psychosocial needs of children in resettlement process - Ajduković, Dean (Array, 2000)
The children in the resettlement process need much more support to fulfill their developmental tasks than is regularly available. It is important to help children not only deal with their war-related stress and trauma, but also give them practical tools regarding the resolution of everyday problems. The challenge is to create effective community-based models and interventions that can help facilitate psychosocial reconstruction of the communities, decrease social tensions among groups that were involved in conflict, provide treatment for the most traumatized individuals, help restore people's faith in themselves and community, help integrate painful collective experiences so that the cycle of violence and victimization can be interrupted. Experiences from the community-based psychosocial assistance program implemented in two resettlement areas in Croatia that have been reintegrated in 1995 are presented. At one location it was implemented over a year period, and at the other locality during two years. The objective was to facilitate psychological and social transition of refugee and displaced children and their families, and to help raise professional competence of care-providers in the resettlement community to take active part in the reconstruction process with regard to children's psychosocial needs and their rights. The program was developed as a model that could be utilized in a number of other communities in which the pre-war population will return